A Two-Dimensional Fornasini-Marchesini Second Model-Based Finite Frequency H∞Static Output Feedback Control - Zoulagh, T (Institute of Electrical and Electronics Engineers Inc., 2021)
In this talk, the Generalized Kalman Yakobovich Popov (GKYP) lemma is used to examine the H∞ Static Output Feedback (SOF) Controller Design with finite frequency (FF) specification for Two-Dimensional (2D) fronasini-Marchesini (FM-II) Discrete Systems. In particular, a novel condition for FF SOF H∞ controller design in terms of Linear Matrix Inequalities is given (LMIs). The current entire-frequency (EF) design is less conservative as a result of this research. Examples from literature are presented to demonstrate the efficacy of the produced findings. © 2021 IEEE.